2014
DOI: 10.1177/0165025414556096
|View full text |Cite
|
Sign up to set email alerts
|

Emotion understanding in preschool children

Abstract: This investigation was aimed at studying the relations between executive functions (EFs) and categorical emotion understanding while controlling for preschoolers' IQ, language ability and theory of mind (ToM). Specifically, we wanted to analyse the association between emotion understanding and set shifting, due to the lack of studies with this EF. Data of 75 children aged 4½ years (52% boys) was collected in two laboratory visits. Emotion understanding was assessed using the Emotion Recognition Questionnaire, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 60 publications
2
17
0
5
Order By: Relevance
“…The MEFS has been used with over 5,000 children and been found to be reliable (Beck, Schaefer, Pang, & Carlson, 2011) and valid (Carlson & Harrod, 2013). This measure also has been validated in clinical populations (Doom et al, 2014; Fuglestad et al, 2014) and at-risk preschoolers (Chu, VanMarle, & Geary, 2013; VanMarle, Chu, Li, & Geary, 2014), is related to emotion understanding in preschoolers (Martins, Osorio, Verissimo & Martins, 2014), and predicts kindergarten readiness and first-grade math achievement over and above IQ (Carlson & Harrod, 2013; Hassinger-Das et al, 2014). Individual items consisted of the child correctly or incorrectly sorting cards into two equidistant boxes affixed with target cards specified by level.…”
Section: Methodsmentioning
confidence: 99%
“…The MEFS has been used with over 5,000 children and been found to be reliable (Beck, Schaefer, Pang, & Carlson, 2011) and valid (Carlson & Harrod, 2013). This measure also has been validated in clinical populations (Doom et al, 2014; Fuglestad et al, 2014) and at-risk preschoolers (Chu, VanMarle, & Geary, 2013; VanMarle, Chu, Li, & Geary, 2014), is related to emotion understanding in preschoolers (Martins, Osorio, Verissimo & Martins, 2014), and predicts kindergarten readiness and first-grade math achievement over and above IQ (Carlson & Harrod, 2013; Hassinger-Das et al, 2014). Individual items consisted of the child correctly or incorrectly sorting cards into two equidistant boxes affixed with target cards specified by level.…”
Section: Methodsmentioning
confidence: 99%
“…Leerkes, Paradise, O'Brien, Calkins, and Lange () found that a cool executive functions factor, indicated by working memory and cool inhibitory control, was significantly related to emotional self‐regulation in 3.5‐year‐olds. However, Liebermann, Giesbrecht, and Müller () and Martins, Osório, Veríssimo, and Martins () did not find support for an association between cool inhibitory control and emotional self‐regulation.…”
Section: Introductionmentioning
confidence: 93%
“…(Bower, 1992). Com o seu desenvolvimento, vai-se notando gradualmente uma cada vez mais complexa diferenciação, identificação e denominação das emoções (Bower, 1992;Maló Machado, Veríssimo, & Denham, 2012;Martins, Osório, Veríssimo, & Martins, 2016). Este processo resulta na especificação e refinamento de emoções básicas (e.g., medo, alegria) surgindo ligadas a estas, novas emoções subordinadas (e.g., orgulho, horror) que se vão diferenciando mais ou menos, num sentido ou noutro consoante as realidades culturais (Bower, 1992;Fischera, Shaverb, & Carnochanc, 1989).…”
Section: As Emoções -Caraterísticas E Desenvolvimentounclassified
“…Na caraterização das emoções um tipologia consistentemente utilizada é a sua divisão em emoções positivas e negativas e que é também uma das primeiras usada pelas crianças em termos de diferenciação e identificação das emoções (e.g., Bower, 1992;Kok & Fredrickson, 2013;Martins et al, 2016;Pekrun, 2006Pekrun, , 2009. A importância desta dicotomia na distinção das emoções é realçada nos trabalhos de Fredrickson (2001de Fredrickson ( , 2003Kok & Fredrickson, 2013), que as considera distintas não só ao nível das caraterísticas como dos seus efeitos diferenciados a curto e longo prazo.…”
Section: As Emoções -Caraterísticas E Desenvolvimentounclassified